Study of cell survival in non adherent conditions - Małecki, Maciej; Sroczyńska, Paulina (Contemporary Oncology/Współczesna Onkologia, 2000)
Cell adhesion to the extracellular matrix (ECM) triggers a cascade of intracellular signalling pathways initiated by a family of integrin receptors. These receptors activate FAK, Ras and MAP kinase cascades to regulate a variety of cellular functions, such as cell proliferation, adhesion, migration and apoptosis. Adhesion of anchorage dependent cells to the ECM is thought to be the crucial factor for their survival. Many tumour cell lines are anchorage dependent, although not to the same degree as normal cells. In this work we were interested in the mechanism of cell survival in non adherent conditions. We investigated some aspects of signal transduction in adherent and non adherent cells of different origin. The cell lines were human ovarian carcinoma cell line (OVP 1O) and human urothelial cell line (HCV-29). We found new information on anchorage-independent behaviour in cells of different origin.